El rol de las Comisiones de la Verdad frente a las democracias represivas de Ecuador y Perú - Jeny Elizabeth Vargas Yangua; Diego Fernando Peñafiel Valencia; Ignacio Alberto Marchán Gavilanes (Bulletin de l'Institut Français d'Études Andines, 2022)
This article makes a comparative analysis of the Transitional Justice processes in Ecuador and Peru, and particularly the role of the truth commissions in the investigation of systematic human rights violations perpetrated in a Cold War context. For the first part, a theoretical reflection on Transitional Justice is developed, emphasizing the scope and limitations of the truth commissions, addressing the recognition of the right for truth and the rescue of historical memory. Then a theoretical approach to the national security doctrine is carried out, highlighting its implementation in the Andean region and the difference with the dictatorships of the Southern Cone. In countries like Ecuador and Peru, the international crimes registered were carried out by democratically elected governments. Finally, the main findings of the Final Reports are described, highlighting differences between Ecuador and Peru.